Scoping Review on Rehabilitation Scoping Reviews - Colquhoun, Heather L; Jesus, Tiago S; O'Brien, Kelly K; Tricco, Andrea C; Chui, Adora; Zarin, Wasifa; Lillie, Erin; Hitzig, Sander L; Seaton, Samantha; Engel, Lisa; Rotenberg, Shlomit; Straus, Sharon E (Archives of physical medicine and rehabilitation, 2020)
To examine the extent, scope, and methodological quality of rehabilitation scoping reviews. A comprehensive list of scoping reviews conducted in the broader health field (inception to July 2014), with a further update of that list (up to February 2017) using similar methods, including searching 9 electronic databases. Articles were included if they were scoping reviews within rehabilitation. Established review methods were used including (1) a PubMed filter detecting rehabilitation content and (2) title-and-abstract screening by 2 independent reviewers applied sequentially to articles from the existing list of scoping reviews and to the updated search results. Full-text articles were reviewed by 1 reviewer, with discrepancies resolved by another after pilot screening with > 80% agreement. Remaining discrepancies were resolved by external experts. Two independent reviewers used piloted and standardized data extraction forms. We screened 1823 records, including 992 full texts, to identify 251 rehabilitation-related scoping reviews. Rehabilitation scoping reviews had an exponential yearly increase since 2008 (r =0.89; P<.01). The literature addressed diverse topics (eg, spread over 43 condition groupings); 43% were published in Canada. Examples of methodological limitations included: 39% of reviews did not cite the use of a methodological framework, 96% did not include the appropriate flow diagram, 8% did not report eligibility criteria, and 57% did not report data extraction details. The increasing popularity of scoping reviews in rehabilitation has not been met by high standards in methodological quality. To increase the value of rehabilitation scoping reviews, rehabilitation stakeholders need to use existing methodological standards for the conduct, reporting, and appraisal of scoping reviews.